THE INFLUENCE OF TRAINING AND JOB COMPETENCY ON EMPLOYEE PERFORMANCE MEDIATED BY MOTIVATION AT PT. PELABUHAN INDONESIA PERSERO REGIONAL AMBON - Mujulifa La Seni; Conchita Valentina Latupapua; Novalien C Lewaherilla (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Employee performance is a critical determinant of organizational success, particularly in state-owned enterprises such as PT. Pelabuhan Indonesia (Persero) Regional Ambon. This study examines the impact of training (X₁) and competency (X₂) on employee performance (Y), with motivation (Z) as a mediating variable, using a quantitative approach and Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that X₁ does not significantly influence Y, either directly or through Z, suggesting that training alone is insufficient to enhance performance without complementary motivational reinforcement. Conversely, X₂ exhibits a strong positive effect on both Y and Z, confirming that competency development is a key driver of performance. Additionally, Z significantly influences Y, validating motivation as a crucial mediating factor between competency and performance. The study highlights the limited effectiveness of training programs unless integrated with skill-based competency development and motivation-enhancing interventions. These results underscore the need for strategic HRM frameworks that combine competency-building with intrinsic and extrinsic motivational incentives to optimize employee engagement and productivity. Future research should further investigate longitudinal effects and industry-specific applications of competency-driven performance models.